University selectivity and returns premium: evidence from Kazakhstan - Kemelbayeva, S. (EDUCATION ECONOMICS VOL.30, NO.3, 270–302, 2022)
More selective universities are presumably better in quality and expected to provide better labour market outcomes for their graduates – returns premia. However, various empirical applications have found that part of it should be attributed to selectivity. Using the data on recent higher education graduates’ entry salaries with a fuzzy regression discontinuity design, this study reveals no apparent difference in the returns one gains by attending more selective and relatively better-funded national universities as opposed to other public HEIs in Kazakhstan, at least during the first year in employment, which may potentially call for a reconsideration of the associated policies.
Keywords: Returns to education; higher education selectivity; Kazakhstan